NSG2 (ORF19.273) Encoding Protein Controls Sensitivity of Candida albicans to Azoles through Regulating the Synthesis of C14-Methylated Sterols - Lv, Quan-Zhen; Qin, Yu-Lin; Yan, Lan; Wang, Liang; Zhang, Chuyue; Jiang, Yuan-Ying (Frontiers in Microbiology, 2018)
Antifungal azole drugs inhibit the synthesis of ergosterol and cause the accumulation of sterols containing a 14α-methyl group, which is related to the properties of cell membrane. Due to the frequent recurrence of fungal infections and clinical long-term prophylaxis, azole resistance is increasing rapidly. In our reseach, Nsg2p, encoded by the ORF19.273 in C. albicans, is found to be involved in the inhibition of 14α-methylated sterols and resistance to azoles. Under the action of fluconazole, nsg2Δ/Δ mutants are seriously damaged in the integrity and functions of cell membranes with a decrease of ergosterol ratio and an increase of both obtusifoliol and 14α-methylfecosterol ratio. The balance between ergosterol and 14α-methyl sterols mediated by NSG2 plays an important role in C. albicans responding to azoles in vitro as well as in vivo. These phenotypes are completely different from those of Nsg2p in S. cerevisiae, which is proved to increase the stability of HMG-CoA and resistance to lovastatin. Based on the evidence above, it is indicated that the decrease of 14α-methylated sterols is an azole-resistant mechanism in C. albicans, which may provide new strategies for overcoming the problems of azole resistance.